Effect of Silica Composition from Rice Husk Ash on The Performace of Absorbing Electromagnetic Wave on Composite of Unsaturated Polyester Resins/Silica - Fauzy, Rizky; Adi, Wisnu Ari; Taryana, Yana; Yusmaniar, Y. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
This study aim is to know the effect of silica composition on the absorption of electromagnetic waves in the composite of unsaturated polyester resins (UPR)/silica. Silica raw materials have been synthesized from the results of rice husk ash extraction. The results of the analysis phase and elementary respective using X-ray diffraction (XRD) and energy dispersive spectroscopy (EDS) show that the extraction of silica has an amorphous phase with a high purity. This silica powders are filler material acts as an electromagnetic waves absorber material and combined with the UPR as a matrix to form a composite. Silica powder varied with several compositions in this composite. The observation of scanning electron microscope (SEM) shows that the silica particles have been distributed evenly in the UPR matrix. Meanwhile the results of testing the absorption of electromagnetic waves at frequency range of 8 GHz - 12 GHz using a vector network analyzer (VNA) show that the addition of silica composition have significant effect on the absorption of electromagnetic waves. The more the silica content in the UPR matrix causes the absorption of electromagnetic waves more increasing. It was concluded that the presence of silica can improve the absorption performance of electromagnetic waves in composite UPR/silica. Keywords: rice husk ash, silica, UPR, composites, electromagnetic wave absorber